Lipids in the intensive care unit: Recommendations from the ESPEN Expert Group. Issue 1 (February 2018) - Calder, Philip C.; Adolph, Michael; Deutz, Nicolaas E.; Grau, Teodoro; Innes, Jacqueline K.; Klek, Stanislaw; Lev, Shaul; Mayer, Konstantin; Michael-Titus, Adina T.; Pradelli, Lorenzo; Puder, Mark; Vlaardingerbroek, Hester; et al.
Summary: This article summarizes the presentations given at an ESPEN Workshop on "Lipids in the ICU" held in Tel Aviv, Israel in November 2014 and subsequent discussions and updates. Lipids are an important component of enteral and parenteral nutrition support and provide essential fatty acids, a concentrated source of calories and building blocks for cell membranes. Whilst linoleic acid-rich vegetable oil-based enteral and parenteral nutrition is still widely used, newer lipid components such as medium-chain triglycerides and olive oil are safe and well tolerated. Fish oil (FO)-enriched enteral and parenteral nutrition appears to be well tolerated and confers additional clinical benefits, particularly in surgical patients, due to its anti-inflammatory and immune-modulating effects. Whilst the evidence base is not conclusive, there appears to be a potential for FO-enriched nutrition, particularly administered peri-operatively, to reduce the rate of complications and intensive care unit (ICU) and hospital stay in surgical ICU patients. The evidence for FO-enriched nutrition in non-surgical ICU patients is less clear regarding its clinical benefits and additional, well-designed large-scale clinical trials need to be conducted in this area. The ESPEN Expert Group supports the use of olive oil and FO in nutrition support in surgical and non-surgical ICU patients but considers that further research is required to provide a more robust evidence base.